2021
DOI: 10.1109/access.2021.3135662
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Implementation of an AI-Based Smart Construction Safety Inspection Protocol in the UAE

Abstract: The safety of workers at construction sites is one of the most important aspects that should be considered while performing their required tasks. Many rules and regulations have been implemented in the UAE to reduce injuries and fatalities in the jobsites. However, the number of accidents continues to increase. For instance, an accident category of fall-from-height is considered as the top cause of injuries and fatalities. Thus, this paper develops a novel technique that monitors the workers whether they are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One notable application is predictive analytics, which leverages historical data and machine learning algorithms to forecast potential project delays, material shortages, and cost overruns [1,9,10]. Another vital area is autonomous construction equipment, such as self-driving bulldozers and excavators, which streamline excavation and grading processes while reducing labour costs [11][12][13]. Computer vision systems enable real-time monitoring of construction sites, enhancing safety by detecting potential hazards and ensuring compliance with safety protocols [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…One notable application is predictive analytics, which leverages historical data and machine learning algorithms to forecast potential project delays, material shortages, and cost overruns [1,9,10]. Another vital area is autonomous construction equipment, such as self-driving bulldozers and excavators, which streamline excavation and grading processes while reducing labour costs [11][12][13]. Computer vision systems enable real-time monitoring of construction sites, enhancing safety by detecting potential hazards and ensuring compliance with safety protocols [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…YOLOv3 overcomes the limitations of YOLOv2 and YOLOv1 by detecting features at three different scales, especially in the detection of smaller objects [25]. [26], where the yellow box in the MRI shows the location of the tumor. Figure 6.…”
Section: Yolov3mentioning
confidence: 99%
“…Figure 6. Architecture of the YOLOv3 model[26], where the yellow box in the MRI shows the location of the tumor. Figure6.…”
mentioning
confidence: 99%
“…Reja et al [3] used deep learning to track construction progress by analyzing images and videos to enhance project management activities and decision-making. Shanti et al [4] demonstrated the use of deep learning for recognizing safety violations at construction sites. Park et al [5] applied deep learning to detect and quantify cracks on surfaces of concrete structures.…”
Section: Introductionmentioning
confidence: 99%